The blast from the past [large type] - Score, Lucy (Score, Lucy. Riley Thorn novels, 2026)
"Riley Thorn and her hot, tattooed, private investigator boyfriend Nick Santiago are all moved in to their new fixer-upper. Not only do they finally have their own place, they also haven't found any new dead bodies on the premises. Yep. It looks like summer is over and so is Riley's bad luck. Or is it? When Nick gives up sleeping and showering to obsess over the cold case that still haunts him, his intrepid business partner Mrs. Penny is calling the investigative shots. It's every bit as bad as you can imagine. Meanwhile, Riley has her hands full fixing up the crumbling crime scene they call home and setting boundaries with the breaking-and-entering octogenarians next door. You know. Normal stuff. But normal comes to a screeching halt when Riley is abducted by a stranger, and her psychic powers go on the fritz. To make matters worse, it becomes clear that Riley's new house guests are either in trouble or are trouble after bad guys deliver a warning with a severed finger. Can Nick and Riley solve the case the old-fashioned way before they all end up in pieces? Or will a surprise birthday party, a dog doody bandit, an accidental arson, and a blast from the past be too much for them to handle?"--